Energy Router Applications in the Electric Power System - Umar, Bashir Musa; Jibril, Yusuf; Jimoh, Boyi; Bala Kunya, Abdullahi; Aliyu, Safiya (Journal of Applied Materials and Technology, 2023)
Energy router is being investigated to replace conventional transformer in the electric grid. Improvement so far observed in use of converter makes possible the intelligent integration between systems with different characteristics’ in terms of frequency and voltage levels as well as exploitation of generation sources and storage systems typically operating in DC. Consequently, it is believed that Energy Router is able to interconnect different portions of electrical networks and at different voltage levels and types. The Energy Router is an assembly of converters isolated by a medium or high frequency transformer. In its design, different voltage levels and types are made available to achieve high results in terms of system integration, efficiency and flexibility. This paper evaluates the main potentials of this technology if widely introduced in the main power system. Starting from the single component description, a couple of possible applications are presented and discussed.